Understanding Students’ Consumption Behavior: The Role of Digital Payment, Financial Literacy, and Lifestyle - Septiani, Atikah; Hia, Angel Christin; Syahira, Adella Devany; Amelia, Rika; Wardani, Wanda Putriana (Talent: Journal of Economics and Business, 2025)
This study explores the shifting consumption behavior in society amidst the rapid digitalization of payment systems, particularly through the use of digital payments, which have become an integral part of the economic activities of the younger generation. The main objective of this study is to evaluate the impact of digital payment usage on consumptive behavior, taking into account the mediating role of financial self-control and the moderating role of financial literacy. A quantitative approach was employed, utilizing primary data collected through questionnaires distributed primarily to university students. The data were analyzed using structural equation modeling (SEM) to identify patterns of relationships among the studied variables. A total of 153 respondents participated in this study. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS software, which enabled comprehensive testing of measurement validity, reliability, and structural relationships among variables. The results indicate that higher intensity of digital payment usage is associated with a greater likelihood of uncontrolled and impulsive consumptive behavior. However, individuals' ability to exercise financial self-control significantly mitigates this negative effect and supports more prudent financial decision-making. On the other hand, financial literacy did not exhibit a significant moderating effect, although it is still conceptually considered important in shaping rational financial attitudes. The discussion highlights the need for the development of digital features that promote financial discipline. Therefore, financial management strategies in the digital era should be holistic, adaptive, collaborative, and oriented toward fostering healthy, balanced, and sustainable consumption behavior.